2014
DOI: 10.3390/ijms150711678
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Health: Food Effects on Gut Microbiota and Disease Control

Abstract: The Mediterranean diet (MD) is considered one of the healthiest dietary models. Many of the characteristic components of the MD have functional features with positive effects on health and wellness. The MD adherence, calculated through various computational scores, can lead to a reduction of the incidence of major diseases (e.g., cancers, metabolic and cardiovascular syndromes, neurodegenerative diseases, type 2 diabetes and allergy). Furthermore, eating habits are the main significant determinants of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 144 publications
1
117
0
8
Order By: Relevance
“…Marlow et al showed that the Mediterranean diet appeared to benefit the health of Crohn's disease patients, reflected by a trend for reduced inflammation biomarkers and normalization of the gut microbiota with increasing Bacteroidetes and Clostridium and decreasing Proteobacteria and Bacillaceae (Marlow et al, 2013). This also suggests that the Mediterranean diet may play important roles in disease control including AD through balancing the gut microbiota (Del Chierico et al, 2014).…”
Section: Diet Gut Microbiota and Admentioning
confidence: 97%
“…Marlow et al showed that the Mediterranean diet appeared to benefit the health of Crohn's disease patients, reflected by a trend for reduced inflammation biomarkers and normalization of the gut microbiota with increasing Bacteroidetes and Clostridium and decreasing Proteobacteria and Bacillaceae (Marlow et al, 2013). This also suggests that the Mediterranean diet may play important roles in disease control including AD through balancing the gut microbiota (Del Chierico et al, 2014).…”
Section: Diet Gut Microbiota and Admentioning
confidence: 97%
“…The Mediterranean diet may positively influence the ageing process (70) by delaying the evolution of cognitive decline linked to Alzheimer's disease (71) and vascular dementia, which is often documented a long time before the clinical diagnosis of dementia (72) . The Mediterranean diet appears to have numerous other health advantages that are still under study, such as lower peripheral artery disease (73) , decreased inflammation and improved endothelial function (74) , improved respiratory fitness (75) and immunity (76) , decreased mental disorders such as depression (77) , as well as improved quality of life (78) . This substantial body of scientific evidence links the Mediterranean diet to the prevention of the main chronic non-communicable diseases.…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…These whole foods contain a variety of polyphenols and plant bioactive compounds that have modifying activities against inflammation, tumorigenesis, and atherogenesis (6). While dietary patterns undoubtedly exert a powerful effect on the gut microbiome (7), there is accumulating evidence that among the beneficial effects of the Mediterranean diet is the ability to positively impact the composition of the gut microbiota (7,8).…”
Section: Introductionmentioning
confidence: 99%